ANALYSIS DU PONT SYSTEM TO ASSESS THE FINANCIAL PERFORMANCE OF PT SARIGUNA PRIMATIRTA TBK PERIOD 2017-2021 - Rully Movizar; Immi Fiska Tarigan (International Journal Management and Economic, 2024)
This research discusses the analysis of financial performance at PT Sariguna Primatirta Tbk for the 2017-2021 period using theDupont systemwhich aims to enable companies to know the causes of increases and decreases in ROI and ROE in companies, so that companies can adopt policies for cost efficiency or increase company sales. The data source used in this research is secondary data obtained fromwebsite company officialhttps://tanobel.com/ andwebsite official Indonesian Stock Exchangehttps://www.idx.co.id The data is in the form of PT Sariguna Primatirta Tbk's financial report for 2017-2021. Based on the research results, the author draws the conclusion thatPT Sariguna Primatirta Tbk's financial performance for the 2017-2021 period is quite good. This is because, of the five variables in the methodDupont systemonlyTotal Asset Turnover (TATO) which is below industry standards, and four other variables, namelyNet Profit Margin (NPM), Return On Investment (ROI), Equity Multiplier (IN), Return On Equity (ROE) is above industry standards.Total Asset Turnover (TATO) is below industry standards because the company's sales in five years often decrease compared to the increase in total assets. So, this shows that the company has not been able to rotate company assets to increase sales properly.